Upaya Meningkatkan Hasil Belajar Matematika Bangun Ruang dengan Menggunakan Model Pembelajaran Kooperatif Tipe Jigsaw - Linda Ismayani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The purpose of this study to determine the improvement of learning outcomes mathematics building materials through the model of cooperative learning type Jigsaw on fourth grade students SD Negeri 46 Lubuklinggau Lesson 2016/2017. The subjects in this study were students of Class IV SD Negeri 46 Lubuklinggau which amounted to 22 students. This study will be conducted on even semesters in the 2016/2017 School Year classes from April to May 2017. This classroom action research has been said to be complete with the proven improvement of learning outcomes Mathematics of building materials Jigsaw Type Co-operative learning model of the academic year 2016 / 2017. Learning mastery increased from pre cycle, cycle I, to cycle II that is 41%, 73%, and 86% respectively. In the second cycle of student learning completeness has been achieved in classical and experienced a very good improvement. Besides, the average value of observation result of student learning activity Cycle II reach 85.45 in very active category Keyword: Learning Outcomes, Jigsaw Type Co-operative Model